Migration of Primordial Germ Cells Is Regulated by miR-430 During Embryonic Development of Japanese Flounder - Wang, Bo; Yang, Fan; Jin, Chaofan; Hu, Jingjie; Qi, Jie; Zhang, Quanqi (Frontiers in Marine Science, 2022)
The origin and migration of primordial germ cells (PGCs) were regulated by miRNA during embryogenesis, but the underlying mechanism in marine teleost species was still unclear. Here, we studied the function of miR-430 in the development and migration of PGCs in Japanese flounder. By co-injecting miR-430 with eGFP-vasa 3’UTR mRNA, we found that miR-430 could cause the mis-localization of PGCs in flounder. Besides, the overexpression of miR-430 also inhibited the expression of three PGC-related genes (nanos3, piwil2 and tdrd7a), both target gene prediction and dual-luciferase reporter assay showed that miR-430 were directly binding on the canonical target site of their 3’UTRs. Significantly, the miR-430 target site of piwil2 3’UTR was necessary for PGC specific expression, where the binding seeds “GCACTTT” sequence mutation lead the distribution of eGFP-piwil2 mRNA turned from PGC-specific (wild-type) to ubiquitous (mutant). These findings will provide further evidence on the role of miR-430 in the regulation of the development and migration of PGCs.